Perceptions of civil servant towards sharia bank service: evidence from employees on public works and spatial planning department in Samarinda city - Swadia Gandhi Mahardika; Muh Shadiqul Fajri AF; Abiyajid Bustami; Rinna Ramadhan Ain Fitriah; Isna Yuningsih (INOVASI, 2023)
The background of this research was the salary distribution for the civil servants. The salary distribution for employees on the Department of Public Works and Spatial Planning or Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) in Samarinda City was from the conventional bank. However, the civil servants mostly used Sharia Bank for their daily activities. The utilization of the Sharia Bank based on the users’ perception. Knowledge and response were the factors to influence this perception. The research aimed to know 1) the perception of civil servants on the Department of Public Works and Spatial Planning in Samarinda City toward the use of Sharia Bank services based on knowledge and response, and 2) the main factor that influenced the civil servants to choose the Sharia Bank. This research was field research with a phenomenology approach. The data collection methods for this research were interviews and documentation. The data was collected from civil servants on the Department of Public Works and Spatial Planning Samarinda City as users of the Sharia Bank services. The research results showed that 1) the perception of civil servants on the Department of Public Works and Spatial Planning in Samarinda City based on the employee’s knowledge and response. The civil servants appraised the Sharia Bank as their first choice. The employees understood about the Sharia Bank such as its products, the bank‟s administration, its strategic place, the Sharia Bank promotion, the service qualities, Sharia Bank‟s facilities, and the fast service transaction. The response was influenced by factors such as culture, technology, social, and psychology. 2) The psychological factor that influences employees using the Sharia Bank services was a self-awareness to have freedom usury. For the civil servants, using the Sharia Bank services brought some benefits such as feel peaceful, secured, and blessed.